A criterion of solvability of resonant equations and construction of their solutions - Boichuk, О. A.; Makarov, V. L.; Feruk, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.983 We establish conditions for the existence and determine the general structure of solutions of resonant and iterative equations in a Banach space and their algorithmic realization.